As-Shifa` Perspektif Tafsir al-Ibris Karya Bisri Mustofa - Khainuddin Khainuddin (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This article aims to explain how As Shifa in the interpretation of Al-Ibriz by KH Bisri Mustofa and how to obtain physical and mental health in the interpretation of Al-Ibriz by KH Bisri Mustofa. He interpreted the verses of shif? 'as medicine for spiritual health only, but there also argued that the Qur'an could not only be used as a medicine for spiritual / mental health (soul and heart) but could also be used as a medicine for health physical. The results of this study show that the Qur'an as a guide book, the Qur'an contains various information about medicine for humans, the Qur'an fulfills the principles of medicine and the rules of treatment. Shif? 'in the Qur'an has a close relationship to physical health. According to Bisri Mustofa, the Qur'an is not only a medicine for liver disease, but the protracted liver disease will cause physical illness known as psychosomatic disease.